The Logical Relationship between No Loss Principle in Islamic Jurisprudence and the Principle of Abuse of Rights in Western Legal Systems - Abbas Karimi; Hadi Shabani Kandsari (پژوهش تطبیقی حقوق اسلام و غرب, 2015)
In this article, the logical relationship between No Loss Principle in Islamic jurisprudence and the principle of Abuse of Rights in French jurisprudence has been put under study. Throughout this article, we show the significance of this principle in Islamic law by clarifying its concepts and criteria in comparison with principle of Abuse of Rights in French Law. In this regard, we show what the criterion, concept and the scope of No Loss Principle and the Principle of Abuse of Rights are. By studying the Quran, Islamic traditions, and the opinions of jurists, we come to the conclusion that term ضرر (Zarar) means material loss whereas ضرار (Ziraar) means immaterial loss accompanied by harassment. The content of No Loss Principle dispenses with detrimental ordinance; and the criterion of the fulfillment of loss applies to unusual damages. The domain of this principle is so broad. It consists of religious state of affairs. It is also used to reject an ordinance by with somebody may inflict damages via the performance of right to somebody else. On the other hand, in French Law, the permission to perform rights is rejected if it is used at the expanse of others. A new theory propounded for abuse of right is unconventionality of created loss and finally has similar criterion with no loss principle. The canal of principle of abuse of right is performance of right and subsequently has a narrower scope in comparison to the No Loss Principle.